Synthesis and characterization of site selective photo-crosslinkable glycidyl methacrylate functionalized gelatin-based 3D hydrogel scaffold for liver tissue engineering - Sk, Md Moniruzzaman (2022)
The presented work outlined the development of a new biocompatible hydrogel material that has potential applications in soft tissue engineering. As a proof of concept, human hepatocytes were used to demonstrate the suitability of this material in providing conducive environment for cellular growth and functional development. Herein, a detailed synthesis of novel gelatin derivatives - photo-crosslinkable glycidyl methacrylate (GMA) functionalized gelatins (Gelatin-GMA), and preparation of three-dimensional (3D) hydrogel scaffolds for the encapsulated Huh-7.5 cells is reported. The Gelatin-GMA biopolymers were synthesized at two different pH values of 3.5 (acidic) and 10.5 (basic) where two different photo-crosslinkable polymers were formed utilizing -COOH & -OH groups in acidic pH, and -NH2 & -OH groups in basic pH. The hydrogels were prepared using an initiator (Irgacure I2959) in the presence of UV light. The Gelatin-GMA biopolymers were characterized using spectroscopic studies which confirmed the successful preparation of the polymer derivatives. Rheological measurement was carried out to characterize the mechanical properties and derive the mesh sizes of the 3D hydrogels. Subsequently, detailed in vitro hepatocyte compatibility and functionality studies were performed in the 3D cell seeded hydrogel platform. The 3D hydrogel design with larger mesh sizes utilizes the advantage of the excellent diffusion properties of porous platform, and enhanced cell-growth was observed, which in turn elicited favorable Huh-7.5 response. The hydrogels led to improved cellular functions such as differentiation, viability and proliferation. Overall, it showed that the Gelatin-GMA based hydrogels presented better results compared to control sample (GelMA) because of the higher mesh sizes in Gelatin-GMA based hydrogels. Additionally, the functional group studies of the two Gelatin-GMA samples revealed that the cell functionalities are almost unaffected even after the tripeptide - Arg-Gly-Asp (RGD) in Gelatin-GMA synthesized at pH 3.5 is no longer completely available.